343 Immune Modulation of Breast Cancer with Zoledronic Acid in Mouse Model. (11th January 2018) - Eng, Hock-Liew; Liu, Hsien; Lin, Tsun-Mei
Abstract: Introduction: Zoledronic acid (ZA), a nitrogen-containing bisphosphonate, has been known to inhibit the expression of RANKL on osteoblasts to inhibit osteoclastogenesis. In the model of bisphosphonate-related osteonecrosis of the jaw, administration of ZA suppressed Treg-cell activity and activated inflammatory Th17 cells. Our previous studies also demonstrated that ZA modulate immunity by inhibiting the expansion, migration, immunosuppressive function and prometastatic ability of Tregs in vitro. In this study, we further confirmed the effects of ZA on the breast tumor cells in vivo. Methods: We inoculated mouse 4T1 breast cancer cells (1 x 106) into the back of BALB/c mice (n = 30), and treated with ZA 100 ug/kg five times every 3 days. The absolute counts and relative ratio of Treg cells (CD4+CD25+) and activated cytotoxic T lymphocytes (CD8+) infiltration in the tumoral area of breast tumor tissue of mice were analyzed. Results and Conclusion: We demonstrated that the ratio of CD4+ CD25+ and CD8+ T-cell infiltration was significantly decreased ( P = .02) after ZA treatment. However, the ZA treatment had no significant effects on inhibiting the tumor growth and metastasis. Taken together, our data show that ZA represents an effective immune modulator for tumor-infiltrating lymphocytes in breast cancer. Conclusion: Here we demonstrated that these napsin A and TTF-1 double-negative lung adenocarcinomas have significantly different molecular profile than classical lung adenocarcinoma published in TCGA. Recurrent mutations FGFR2, GNA11, GNAQ, and PTEN were associated with these tumors. This study also indicated that targeted NGS could potentially identify novel mutations with available clinical trials.